The role of the user within the medical device design and development process: medical device manufacturers' perspectives - Money, Arthur G.; Barnett, Julie; Kuljis, Jasna; Craven, Michael P.; Martin, Jennifer L.; Young, Terry (Biomed Central, 2011)
Background